Infantile Nystagmus Syndrome—Associated Inherited Retinal Diseases: Perspectives from Gene Therapy Clinical Trials - Xiaoming Gong; Richard W. Hertle (Life)
Inherited retinal diseases (IRDs) are a clinically and genetically diverse group of progressive degenerative disorders that can result in severe visual impairment or complete blindness. Despite their predominantly monogenic inheritance patterns, the genetic complexity of over 300 identified disease-causing genes presents a significant challenge in correlating clinical phenotypes with genotypes. Achieving a molecular diagnosis is crucial for providing patients with definitive diagnostic clarity and facilitating access to emerging gene-based therapies and ongoing clinical trials. Recent advances in next-generation sequencing technologies have markedly enhanced our ability to identify genes and genetic defects leading to IRDs, thereby propelling the development of gene-based therapies. The clinical success of voretigene neparvovec (Luxturna), the first approved retinal gene therapy for RPE65-associated Leber congenital amaurosis (LCA), has spurred considerable research and development in gene-based therapies, highlighting the importance of reviewing the current status of gene therapy for IRDs, particularly those utilizing adeno-associated virus (AAV)-based therapies. As novel disease-causing mutations continue to be discovered and more targeted gene therapies are developed, integrating these treatment opportunities into the standard care for IRD patients becomes increasingly critical. This review provides an update on the diverse phenotypic–genotypic landscape of IRDs, with a specific focus on recent advances in the understanding of IRDs in children with infantile nystagmus syndrome (INS). We highlight the complexities of the genotypic–phenotypic landscape of INS-associated IRDs, including conditions such as achromatopsia, LCA, congenital stationary night blindness, and subtypes of retinitis pigmentosa. Additionally, we provide an updated overview of AAV-based gene therapies for these diseases and discuss the potential of gene-based therapies for underlying IRDs that lead to INS, offering a valuable resource for pediatric patients potentially eligible for ongoing clinical trials.